Implementing digital neuroscience in special-needs-teacher education: exploring student-teachers’ multifaceted learning outcomes related to teaching children with neurodevelopmental disorders - Frei-Landau, Rivi; Grobgeld, Etty; Guberman, Raisa (Frontiers in Psychology, 2023)
Introduction In recent decades, there has been increased use of neuroscience in teacher education, which refers to applying knowledge from brain science to teaching. Similarly, digital learning has been extensively integrated into teacher education, particularly in light of the COVID-19 pandemic. However, the benefits of assimilating educational neuroscience into special-education training—particularly using digital platforms–have yet to be examined. The current study explored the use of digitally-delivered educational neuroscience, related to neurodevelopmental disorders (ND), in teacher education, to gain insight into the learning outcomes alongside the contribution of the digital platform. Methods Employing a qualitative approach, we recruited 193 student-teachers who learned a digital ND-related neuroscience course. Data collection included open-ended reflections, open-ended story questions and five focus groups – all of which were analyzed using content analysis. Results Findings revealed a process involving four learning outcomes: understanding brain-based mechanisms of ND, enhanced empathy, extended perception of teachers’ professional role, and the design of pedagogical adaptations. The analysis also pointed out the various ways in which the digital platform facilitated these learning outcomes. Discussion The study provides theoretical insight into the role of digitally-delivered educational neuroscience in the service of inclusion. It further discusses the practical implications of using digitally-delivered educational neuroscience in teacher education to promote an inclusive pedagogy and best practices.